2014
DOI: 10.1007/s12040-014-0488-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Indicator’ carbonaceous phyllite/graphitic schist in the Archean Kundarkocha gold deposit, Singhbhum orogenic belt, eastern India: Implications for gold mineralization vis-a-vis organic matter

Abstract: Carbonaceous rocks in the form of graphitic schist and carbonaceous phyllite are the major host rocks of the gold mineralization in Kundarkocha gold deposit of the Precambrian Singhbhum orogenic belt in eastern India. The detection of organic carbon, essentially in the carbonaceous phyllite and graphitized schist within the Precambrian terrain, is noted from this deposit. A very close relationship exists between gold mineralization and ubiquitous carbonaceous rocks containing organic carbon that seems to play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Organic rich metasedimentary rocks act as a trap as well as a source of valuable elements such as Au, Ag and Bi (Large et al 2011;Hazarika et al 2013;Sahoo and Venkatesh 2014). The organic matter within carbonaceous metasedimentary rocks indicates reducing conditions favourable for the formation of diagenetic pyrites.…”
Section: Role Of Organic Mattermentioning
confidence: 99%
“…Organic rich metasedimentary rocks act as a trap as well as a source of valuable elements such as Au, Ag and Bi (Large et al 2011;Hazarika et al 2013;Sahoo and Venkatesh 2014). The organic matter within carbonaceous metasedimentary rocks indicates reducing conditions favourable for the formation of diagenetic pyrites.…”
Section: Role Of Organic Mattermentioning
confidence: 99%
“…More over, or ganic mat ter dispersed within phyllite was ana lysed for the first time in search for biomarkers to de ter mine its or i gin. While car bo na ceous phyllites are rel a tively com mon, there are only few pa pers on organic mat ter in those rocks fo cused on the or ganic mat ter role in the ore-form ing pro cesses (Sahoo and Venkatesh, 2014;da Silva Nogueira de Matos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The other important greenstone schist belt of DhV enriched with gold (Au) and other mineralization is located in the Singhbhum Craton of the Eastern India (Mazumder 2005). Kundarkocha gold deposit (22 • 10 N, 86 • 16 E) has proven evidences of gold mineralization within the Precambrian Singhbhum orogenic belt in the Eastern India (Sahoo and Venkatesh 2014). Recently, Jha et al (2015) reported the occurrence of invisible gold within the North Singhbhum Mobile Belt of Singhbhum crustal province by petrographic, SEM and EPMA studies.…”
Section: Introductionmentioning
confidence: 99%